Come varia il clima? Una mostra sul presente e futuro del nostro pianeta - Salizzoni, Emma (Ri-Vista. Research for landscape architecture, 2015)
The title of the exhibition mounted at the Museo Regionale di Scienze Naturali of Turin, “Times are changing: current knowledge and future scenarios of climate change,” is explicative of the authors’ (Luca Mercalli and Claudio Cassardo) main purpose: making the visitor aware both of climate change already occurring - including its effects at global and local levels - and of possible future scenarios. If Arctic and Antarctic, alpine, coastal and rural landscapes show the first signs of climate change (primarily related to global warming) already today, at the end of the century these landscapes will have changed even more dramatically. In order to minimize damages a prompt turnabout and avoidance of the so-called “Titanic syndrome,” i.e. denying a problem which is now evident, are needed.